Advances in agronomy. - Sparks, Donald L., 1953- (Advances in Agronomy., 2008)
Advances in Agronomy continues to be recognized as a leading reference and a first-rate source for the latest research in agronomy. As always, the subjects covered are varied and exemplary of the myriad of subject matter dealt with by this long-running serial. * Maintains the highest impact factor among serial publications in Agriculture * Presents timely reviews on important agronomy issues * Enjoys a long-standing reputation for excellence in the field.